ENVIRONMENTAL REGULATION IN CORPORATE CSR PRACTICES IN INDONESIA: ENVIRONMENTAL REGULATION IN CORPORATE CSR PRACTICES IN INDONESIA - Wibawani, Susanti Arsi; Prasetyo, Dedy Ardian; Suasungnern, Sineenat (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This article explores the influence of environmental legislation on corporate social responsibility in Indonesia. It aims to clarify the regulatory framework surrounding corporate social responsibility, assess how failure to adhere to environmental laws affects corporate reputation and performance, and identify the difficulties companies encounter while implementing corporate social responsibility. The research adopts a normative legal perspective, involving a thorough examination of pertinent laws and regulations, including the 1945 Constitution, Law Number 40 of 2007 concerning Limited Liability Companies, and Government Regulation Number 47 of 2012. Data gathered through desk research and descriptive legal analysis provides a detailed understanding of the relationship between legal frameworks and corporate social responsibility practices in Indonesia. The findings indicate that the corporate social responsibility regulatory framework encourages companies to meet environmental legal requirements, positively impacting corporate reputation. Conversely, non-compliance can damage reputation and public perception, consequently affecting financial outcomes. Companies also face various obstacles in implementing corporate social responsibility, such as insufficient regulatory support and limited resources. Recommendations for companies include enhancing education on corporate social responsibility and fostering collaboration with stakeholders to develop sustainable business practices. These insights are valuable not only for Indonesia but also for other nations examining the link between environmental legislation and corporate social responsibility.